2016
DOI: 10.1016/j.jpor.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Micro-shear bond strength of different resin cements to ceramic/glass-polymer CAD-CAM block materials

Abstract: Use of appropriate resin cement systems with different ceramic/glass-polymer materials might promote the bonding capacity of these systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(119 citation statements)
references
References 26 publications
6
108
1
4
Order By: Relevance
“…The application of HF acid partially dissolves the glass phase and provides undercuts in the micrometer scale for better micromechanical interlocking with a composite cement. However, the recently published working instruction of the International Academy for Adhesive Dentistry (IAAD) confirms the finding of the other laboratory studies and recommends pretreatment via HF acid etching and application of a silane [41,42] The silica-based ceramic part of the hybrid ceramic seems to determine the best choice of surface pretreatment [43].…”
Section: Discussionmentioning
confidence: 61%
“…The application of HF acid partially dissolves the glass phase and provides undercuts in the micrometer scale for better micromechanical interlocking with a composite cement. However, the recently published working instruction of the International Academy for Adhesive Dentistry (IAAD) confirms the finding of the other laboratory studies and recommends pretreatment via HF acid etching and application of a silane [41,42] The silica-based ceramic part of the hybrid ceramic seems to determine the best choice of surface pretreatment [43].…”
Section: Discussionmentioning
confidence: 61%
“…In addition, universal bonding material was used as a primer because it contains various functional components, such as 10-methacryloxydecyl dihydrogen phosphate (MDP) or silane, in addition to the components present in the previously widely used primer. Moreover, a previous study of the bonding of hybrid ceramic found that the bonding strength was higher when the adhesive solution contained MDP than when it contained only silane 16) . Additionally, it was considered that silane could be helpful in bonding because hybrid ceramic also contains silica filler.…”
Section: Discussionmentioning
confidence: 94%
“…Cekic‐Nagas et al evaluated the effect of hydrofluoric acid treatment on the micro‐shear bond strength of 3 resin cements to 3 different hybrid materials. 1.5‐mm thickness samples of PICN (Vita Enamic), nano‐ceramic resin (Lava Ultimate) and nano‐ceramic (Cerasmart) were divided into 2 groups, according to the surface treatment: wet‐ground with silicon carbide abrasive papers or etching with hydrofluoric acid.…”
Section: Mechanical and Adhesive Propertiesmentioning
confidence: 99%